2022
DOI: 10.1210/endrev/bnac016
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Face of Turner Syndrome

Abstract: Turner syndrome is a condition in females missing the second sex chromosome (45,X) or parts thereof. It is considered a rare genetic condition and is associated with a wide range of clinical stigmata, such as short stature, ovarian dysgenesis, delayed puberty and infertility, congenital malformations, endocrine disorders, including a range of autoimmune conditions and type 2 diabetes and neurocognitive deficits. Morbidity and mortality is clearly increased compared with the general population and the average a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
1
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(104 citation statements)
references
References 419 publications
3
90
1
10
Order By: Relevance
“…Despite an incidence of one in 2,000 females for TS and one in 660 males for KS (Nielsen and Wohlert, 1991;Berglund et al, 2020), the underlying pathophysiology for both syndromes is largely unknown. Recent studies have demonstrated that changes in the transcriptome and methylome may explain part of the biological mechanisms underlying the phenotypes of sex chromosome aneuploidies (SCAs) (Sharma et al, 2015;Raznahan et al, 2018;Zhang X. et al, 2020;Gravholt et al, 2022). Based on fibroblast cell lines, peripheral blood mononuclear cells (PBMCs), amniotic fluid cells and pluripotent human cell lines, an altered expression of genes from both autosomes and sex chromosomes, in part due to global methylation changes, has been suggested in TS (Bakalov et al, 2009;Zhang et al, 2013;Massingham et al, 2014;Rajpathak et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite an incidence of one in 2,000 females for TS and one in 660 males for KS (Nielsen and Wohlert, 1991;Berglund et al, 2020), the underlying pathophysiology for both syndromes is largely unknown. Recent studies have demonstrated that changes in the transcriptome and methylome may explain part of the biological mechanisms underlying the phenotypes of sex chromosome aneuploidies (SCAs) (Sharma et al, 2015;Raznahan et al, 2018;Zhang X. et al, 2020;Gravholt et al, 2022). Based on fibroblast cell lines, peripheral blood mononuclear cells (PBMCs), amniotic fluid cells and pluripotent human cell lines, an altered expression of genes from both autosomes and sex chromosomes, in part due to global methylation changes, has been suggested in TS (Bakalov et al, 2009;Zhang et al, 2013;Massingham et al, 2014;Rajpathak et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas misclassification would have decreased our study power and as such, our robust association of CRELD1 is likely a valid finding. We opted to include all individuals with a karyotypically-confirmed diagnosis of TS given the lack of robust karyotype-phenotype correlation in TS, and the possibility of somatic mosaicism in those with only a 45,X cell line (Gravholt et al 2022 ; Youssoufian and Pyeritz 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Turner syndrome (TS) is a common, non-heritable genetic disorder affecting ~ 1 in 2000 females. TS is caused by a complete or partial absence of the second sex chromosome (Gravholt et al 2022 ). Individuals with TS have one or more clinical manifestations, including short stature and ovarian insufficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of girls with Turner syndrome with spontaneous menarche achieve unassisted pregnancy, but most develop early secondary amenorrhea and ovarian failure. Rates of unassisted pregnancy are reported as less than 8% [1 ▪▪ ], yet a few single-centre studies have reported unassisted pregnancy rates and live birth rates as high as 13.5% [33 ▪▪ ,34] and 7.6–11.5% [33 ▪▪ ], respectively, with the preponderance seen in 45,X/46,XX karyotypes. These are obviously selected populations of girls with Turner syndrome.…”
Section: Epidemiologymentioning
confidence: 99%